2014
DOI: 10.1007/s00248-014-0384-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Vaginal Lactobacilli with Potential Probiotic Properties Isolated from Women in North Lebanon

Abstract: The aim of this work was to study the diversity of vaginal lactobacilli in Lebanese women and to evaluate the antagonism, hydrophobicity, and safety characteristics of these strains. This study was performed on samples from 135 women who visited a gynecology clinic in the north of Lebanon, between September 2012 and January 2013. From these samples, 53 different isolates of vaginal lactobacilli were collected from vaginal swabs and identified using biochemical and molecular methods. The use of genotypic Rep-PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 54 publications
4
66
0
Order By: Relevance
“…This ability is higher in acid environments and represents the first step during the formation of biofilms by lactobacilli (Juarez-Thomas et al, 2005). As in other studies (Gil et al, 2010;Kassaa et al, 2014), the present results revealed different levels of auto-aggregation of the lactobacilli, suggesting that these levels depend on the strain and not on the species.…”
Section: Hydrogen Peroxide and Lactic Acid Productionsupporting
confidence: 88%
“…This ability is higher in acid environments and represents the first step during the formation of biofilms by lactobacilli (Juarez-Thomas et al, 2005). As in other studies (Gil et al, 2010;Kassaa et al, 2014), the present results revealed different levels of auto-aggregation of the lactobacilli, suggesting that these levels depend on the strain and not on the species.…”
Section: Hydrogen Peroxide and Lactic Acid Productionsupporting
confidence: 88%
“…The potential of Lactobacillus species to inhibit pathogens of clinical importance such as S. aureus had been evaluated before. Accordingly, Al Kassaa et al (2014) showed that L. fermentum CMUL054 and L. plantarum CMUL140 were active against S. aureus ATCC33862 [23]. Moreover, Hor and Liong (2014) analyzed 87 lactic acid bacteria strains and three strains of bifidobacteria, and found that all strains inhibited the growth of S. aureus by 0.5 to 34.2 %; L. fermentum and L. plantarum , which were isolated from milk, inhibited growth by around 20 % [24].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Hor and Liong (2014) analyzed 87 lactic acid bacteria strains and three strains of bifidobacteria, and found that all strains inhibited the growth of S. aureus by 0.5 to 34.2 %; L. fermentum and L. plantarum , which were isolated from milk, inhibited growth by around 20 % [24]. Although inhibition of S. aureus by lactic bacteria has been reported in many studies [2326], few of them have calculated the MIC from extracellular bacterial extracts. This has made it difficult to assess the extracts’ inhibitory action.…”
Section: Resultsmentioning
confidence: 99%
“…Lactobacillus -dominated microbiota is thought to be a valuable biomarker for vaginal health since the Lactobacillus species can create a barrier against pathogen invasion (Petrova et al, 2015). L. crispatus , L. gasseri , and L. jensenii were the most frequently isolated species in the vagina of healthy women (Pendharkar et al, 2013; Al et al, 2014; Madhivanan et al, 2015), where C. albicans is often a minority co-habitant of vaginal microbiota. In this study, we investigated how these three Lactobacillus species affected C. albicans growth and yeast-to-hyphae transition, which are implicated in its pathogenesis.…”
Section: Discussionmentioning
confidence: 99%